Avant-garde approaches to historical biographical ruptures: on Horst Bienek’s and Oskar Pastior’s memory work on the Gulag - Yamamoto, Hiroshi (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
In my paper, I will attempt to explore the contributions that can be attributed to Horst Bienek and Oskar Pastior in the context of German and international Gulag literature. Their biographies have a number of similarities: Both were socially stigmatized as homosexuals in the GDR and Romania, they were both deported to Stalinist labour camps at around the age of 20, and in this way cheated of their youth. However, they did not initially want to explicitly mention these biographical breaks in their literary works. A close analysis of Pastior’s volume of poetry (Speckturm, 2009) and Bienek’s novel (Die Zelle, 1968) reveals how the two authors approached the profound ruptures in their personal and collective experience of history in an avant-garde style rather than a conventional way of storytelling.